Exploring the Experiences of Single Parents and the Impact of Divorce on Children: A Qualitative Case Study in a Selected City of the Maldives - Mariyam Shahuneeza Naseer; Shafiu Ali (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2026)
This qualitative case study investigates the effects of divorce on children and single parents in a city in the Maldives. The research employed purposive sampling to gather data from divorced single parents with children under 18, analyzing the information using thematic analysis. The results indicate significant disruptions in the daily routines and responsibilities of most single parents, with many feeling overburdened and distressed. Psychological issues, such as isolation, panic attacks, and depressive symptoms, were commonly reported, often exacerbated by economic difficulties. Single parents faced challenges in balancing their personal, emotional, and financial responsibilities, which contributed to heightened stress. The study also highlighted the importance of available support systems, including resources and assistance, in alleviating the negative consequences of divorce on both parents and children. Healthy co-parenting relationships were identified as essential in reducing stress and promoting better outcomes for children post-divorce. The findings emphasize the need for comprehensive guidelines and mechanisms to support single-parent families, ensuring they receive adequate help to navigate the challenges of marital breakdowns. By addressing these needs, it is possible to mitigate the long-term impact of family dissolution on both parents and their children, enhancing their overall well-being and stability in the face of adversity.